Treatment of refractory amblyopia with levodopa associated with full-time occlusion in the dominant eye - Ribeiro,Mariana Zaira Moraes Lima (2019)
Abstract Purpose: To evaluate visual outcomes of levodopa treatment associated with full occlusion of the dominant eye in patients with refractory amblyopia. Methods: A prospective study of 19 attended patients who were subject to treatment with Levodopa and Carbidopa on doses of 0.7mg/kg/day, a ratio of 4:1 divided into three daily doses for 5 weeks, combined with full occlusion (24 hours/day) of the dominant eye. The ophthalmologic exam from previous consultations up to treatment and after 8 weeks of therapy were collected from medical record data. Patients who had completed treatment for more than 12 months were included for complete eye examination. Results: The mean age before treatment with levodopa was 11.0 ± 4.2 years old (varying from 7 to 23 years). The best-corrected visual acuity (Snellen chart) of the amblyopic eye before treatment was 0.24 (0.6 in logMAR) ± 0.16, after 8 weeks of treatment it was 0.47(0.3 in logMAR) ± 0.33, while during the final evaluation it was 0.46 (0.3 in logMAR) ± 0.34. There was a statistically significant improvement in vision after 8 weeks of therapy which was maintained until the final evaluation (p = 0.007). Conclusion: Levodopa/Carbidopa therapyat doses of 0.7 mg/kg/day at a ratio of 4:1 divided in three daily doses, associated with full occlusion of the dominant eye during 5 weeks had a significant improvement on the visual acuity of the amblyopic eye, and persisted up to 1 year after the treatment.